2015
DOI: 10.1080/09540121.2015.1100703
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of factors impacting cervical cancer screening among low-income women living with HIV-AIDS

Abstract: Very little is currently known about factors impacting the prevalence of cervical cancer screening among women living with HIV-AIDS (WLHA). To better understand this issue, we surveyed low-income, medically underserved women receiving subsidized gynecologic care through an integrated HIV clinic. A self-administered questionnaire was completed by 209 women who self-identified as HIV positive. A total of 179 subjects (85.7%) reported having had a Pap test in the last three years. The majority of WLHA (95%) knew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
7
17
6
Order By: Relevance
“…In this study, the uptake of premalignant cervical cancer screening among HIV positive women was 10% which is nearly similar to that of the studies conducted in Addis Ababa 12% [ 14 ] and Nigeria 9% [ 15 ]. However, this finding is lower than the study findings in Kenya 84% [ 9 ], South Africa 32% [ 10 ], Italy 91% [ 11 ] and 54% [ 16 ], Canada 82% [ 17 ], and USA 84% [ 18 ], 78% [ 19 ], 85.6% [ 20 ]. This variation could be due to different socio demographic and economic status of the study participants as well as the countries.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the uptake of premalignant cervical cancer screening among HIV positive women was 10% which is nearly similar to that of the studies conducted in Addis Ababa 12% [ 14 ] and Nigeria 9% [ 15 ]. However, this finding is lower than the study findings in Kenya 84% [ 9 ], South Africa 32% [ 10 ], Italy 91% [ 11 ] and 54% [ 16 ], Canada 82% [ 17 ], and USA 84% [ 18 ], 78% [ 19 ], 85.6% [ 20 ]. This variation could be due to different socio demographic and economic status of the study participants as well as the countries.…”
Section: Discussioncontrasting
confidence: 59%
“…Although there was heterogeneity in the methodology employed in these studies, the results were similar to the present study because the studies focused on women and the conceptual basis could be linked to the HBM. Ogunwale et al explained that HIV-positive women who had not had cervical cancer screening were younger and had multiple sexual partners or had had sexual intercourse with a man with multiple sexual partners [ 37 ]. It is well documented that in Ghana, and other African societies, men tend to dominate affairs of women at the household level, including in decisions about seeking preventive healthcare [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven that information is a key component to increasing screening uptake among women in LMIC. 71 , 74 , 75 While a study conducted in Ethiopia has found that women are 4 times more likely to undergo CC screening if they have previously been diagnosed with a sexually transmitted disease, another study in Uganda has shown that having multiple medical appointments for HIV and screening-related services can generate a considerable amount of stress and confusion, thus discouraging screening participation. 71 , 72 In addition, not knowing how a screening procedure is performed is responsible for speculations and misconceptions on the CC prevention pathway.…”
Section: Screening Uptakementioning
confidence: 99%
“… 76 Growing evidence shows the importance of informing not only the women, but also their male partners, as their support can significantly influence the women’s decision to undergo screening. 74 , 75 One way to ensure the correct transmission of information and to retain patients in health care is by building strong provider–patient relationships, especially for patients with multiple medical and social needs. 73 …”
Section: Screening Uptakementioning
confidence: 99%